Impact of Chronic Kidney Disease on Major Adverse Cardiac Events in Patients with Acute Myocardial Infarction: A Retrospective Cohort Study - Andishmand, Abbas; Zolfeqari, Ehsan; Namayandah, Mahdiah Sadat; Ghaem, Hossein Montazer (Journal of Cardiology and Cardiovascular Medicine, 2024)
Background: Acute Myocardial Infarction (AMI) results in a reduction in patients’ life expectancy. Different risk factors affect the risk of Major Adverse Cardiac Events (MACE). Although the role of kidney dysfunction in patients with Chronic Kidney Disease (CKD) in cardiac events has been identified, many patients with AMI are unaware of their underlying kidney disease. This study aimed to compare the incidence of adverse cardiovascular events and identify predictors of major adverse cardiovascular events in the medium term among patients with and without renal dysfunction following AMI. Methods: This retrospective cohort study was conducted on 1039 patients who were hospitalized for Acute Myocardial Infarction (AMI) between 2018 and 2019. The patient cohort comprised 314 women (mean age: 69.8 ± 13.2 years) and 725 men (mean age: 60.5 ± 13.8 years). Patient data were obtained from the registry of patients with acute myocardial infarction and the participants were followed up for a minimum of one year following hospital discharge to assess the incidence of MACE. Results: The study found that patients with a Glomerular Filtration Rate (GFR) level below 60 had a significantly higher mortality rate than those with a GFR level of 60 or above (15.7% vs. 3.5%, p < 0.0001). The multivariate analysis showed that Diabetes Mellitus (DM), GFR, and Non-ST Elevation Myocardial Infarction (NSTEMI) are significant risk factors for cardiovascular events. (p = 0.016, p = 0.015, p = 0.006 respectively), while variables such as sex, age, and Hypertension (HTN) were not significant risk factors. There was a negative correlation between GFR and death (0.241 - = r, p < 0.0001) Conclusion: This study highlights the importance of detecting kidney disease during an AMI and managing risk factors for cardiovascular disease to improve health outcomes and reduce the risk of mortality.